Análisis de los casos existentes de redes de valor de ciclo cerrado en las empresas manufactureras del sector textil, calzado, aparatos eléctricos y electrónicos, automotriz y petróleo de Bogotá D.C. (2019)
In the development of this project it was proposed to work in the first instance in an exploratory phase, where existing cases of closed-loop supply chain are searched through secondary sources, where a simple triangulation is carried out to identify the manufacturing companies of the Automotive sector, Electrical and Electronic Apparatus, Footwear, Textile and Petroleum; these five sectors are chosen because they are those that contribute to the economic GDP of the country, and they stand out in the city of Bogotá. In second instance, the validation of the supply chain of each of the identified companies is carried out, which are armed during the development of the project, this in order to organize the structure and identify the functioning of each one of them; It is also possible to identify the actors, roles and others in each one of the structural dimensions of the closed-loop supply chain. Finally, it is possible to identify the integration techniques with clients and suppliers, which were inferred in some cases, but this research gives way to guide other researchers to complement their knowledge.